Self-regulated learning predictors of academic performance and strategies in resolving barriers to learning (IR) - Sam Foong (2015)
The purpose of this study was to determine the underlying constructs of an instrument to measure self-regulated learning (SRL), examine the correlation between SRL and academic performance, determine the SRL predictors of academic performance and how gender and age moderated this relationship among nontraditional learners (n=519) in the Primary School Graduate Program (PGSR). Factor analyses, Pearson bivariate correlation, linear regression analysis and moderated multiple regression analyses were performed. Additionally, this study examined the barriers to learning and how SRL could be utilized to resolve these barriers. The items in the Self-Regulated Learning Questionnaire (Sf-ReLQ) was found to comprise a robust scale. Findings revealed that there was a moderately significant relationship between SRL and academic performance. An intriguing finding was the insignificant negative correlation of time study management and academic performance. Overall results of the multiple regression analyses indicated that the set of SRL variables predicted almost 33.4% of the cumulative grade point average and the best predictors of students academic performance were Internet Self-efficacy and Rehearsal. The results also suggested that value motivation was the only self-regulatory strategy whose relationship with academic performance was moderated by age. However, the moderating effect of gender was not found. In-depth interviews of learners (n=8), their spouses (n=7) and lecturers (n=6) revealed that these PGSR learners faced situational, institutional and dispositional barriers to learning. What was inherent in all the respondents perspectives that emerged were summarized in four identifiable themes on strategies utilized to resolve these barriers. In conclusion, the present study provided useful information for educational providers about the importance of SRL in balancing work, family and student roles. This implies that there is a need for attention to be paid to SRL and more importantly it provides awareness and considerations to teach nontraditional learners on how to be a self-regulated learner.